1995
DOI: 10.1073/pnas.92.9.3650
|View full text |Cite
|
Sign up to set email alerts
|

Hormones and mammary carcinogenesis in mice, rats, and humans: a unifying hypothesis.

Abstract: An attempt has been made to put forward a unifying hypothesis explaining the role hormones play in the genesis of mammary cancers of different phenotypes and genotypes in mice, rats, and humans. Most mammary cancers in these species originate in luminal mammary epithelial cells lining the mammary ducts and alveoli. These cancers are histopathologically diverse and are classified on the basis of growth requirements as hormone-dependent or hormone-independent tumors. In most strains of mice, mammary cancers at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
253
0
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 377 publications
(262 citation statements)
references
References 93 publications
5
253
0
1
Order By: Relevance
“…Oestrogens stimulate normal mammary epithelial and tumour cell proliferation (Nandi et al, 1995), also when administered neonatally (Hilakivi-Clarke et al, 1997a, b). In vitro and in vivo studies show that alcohol increases normal and malignant mammary cell In utero alcohol exposure and breast cancer risk L Hilakivi-Clarke et al proliferation .…”
Section: Discussionmentioning
confidence: 99%
“…Oestrogens stimulate normal mammary epithelial and tumour cell proliferation (Nandi et al, 1995), also when administered neonatally (Hilakivi-Clarke et al, 1997a, b). In vitro and in vivo studies show that alcohol increases normal and malignant mammary cell In utero alcohol exposure and breast cancer risk L Hilakivi-Clarke et al proliferation .…”
Section: Discussionmentioning
confidence: 99%
“…Together with the fact that only a small percentage of mammary epithelial cells express ERa (Petersen et al, 1987;Ricketts et al, 1991), it has been suggested that breast cancer may initiate from ER-positive cells but become ER-negative and estrogen-independent in its growth at later stages (Moolgavkar et al, 1980). The observation that mammary tumors arise in both ERKO and ovariectomized mice supports an alternative model that a fraction of breast cancers may directly evolve from ERa-negative cells (Nandi et al, 1995), an idea that needs to be tested with other oncogenic transgenes.…”
Section: Hormonal and Stromal In¯uences On Wnt-1-induced Hyperplasia mentioning
confidence: 95%
“…Prolonged exposure to estrogens is a major etiologic factor in the causation of estrogenmediated cancers (116,117). Two prevailing hypotheses regarding the etiology of estrogen-mediated cancers prevail in the literature.…”
Section: Contribution Of Polymorphisms To Increased/ Decreased Riskmentioning
confidence: 99%